Rancang Bangun Standar Operasional Prosedur (SOP) Aplikasi Layanan Syariah Berbasis Web Pada Koperasi Warga Polban Di Bandung - Purwihartuti, Koernia; Karnawati, Hennidah; Syakrani, Nurjannah; Kristianingsih, Kristianingsih; Angestiwi, Tiafahmi; Firmansyah, Yayan; Wisnuadhi, Bambang; Mauludi , Hasbi Assidiki (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2024)
Currently Koperasi Warga POLBAN (kwp) has carried out increased preparation activities for the transition from conventional USP to Sharia. This community service activity is a continuation of community service 2023. The reviewer's suggestion for community service 2024 is that there is continuity in creating web-based Sharia service applications. Making Sharia service applications must follow the Sharia service SOP, while KWP does not yet have a Sharia service SOP. The purpose of this community service is to produce the design and creation of Sharia service applications using digital web applications in accordance with the Syariah-based Service Operational Procedure Standard (SOP). The design of the SOP digital application is aligned with the aspects contained in the AD and annual members meeting which are applied to the KWP. The method used is an appropriate technology program in collaboration with KWP. In this program, KWP provides the data needed for preparing SOPs. In order to collect the necessary data, observations and interviews were carried out to observe the routine activities of service units in KWP, interviews with administrators and managers regarding the real conditions faced, surveys with KWP members to find out members' opinions regarding the content of Sharia service SOPs before they were input into the digital application. The result is a digital application web for sharia services based on SOPs that have been tested on representatives of members, administrators, supervisors and KWP managers. The trial showed that the sharia service web can be operated well and easily according to their expectations.